Hate Speech, Buzzers, and Islamic Groups: Power Plays in Indonesia 2024 - Haq, Mochamad Ziaul (International Journal of Nusantara Islam, 2025)
This study aims to analyze the shifting causes of hate speech on social media during Indonesia's 2024 political year, from individual motivations to structural factors involving economic and political interests, particularly in the context of religion and culture-based hate speech. It also examines how Islamic mass organizations—such as the Indonesian Ulama Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah—respond to the phenomenon of buzzers spreading hate through religious narratives and political identity. This research uses a qualitative approach, employing online observation, in-depth interviews, and literature review. The main findings reveal that hate speech does not solely stem from ideological fanaticism but also from economic pressures and a well-organized digital political architecture. Buzzers operate as paid agents within a content-production system that profits from hate, rather than acting on personal or ideological impulses. Meanwhile, the responses of Islamic organizations remain largely normative and moralistic. However, groups like NU have begun to adopt more structural interpretations of the issue. Despite this shift, the absence of systematic digital strategies and economic empowerment efforts has prevented these responses from addressing the root causes. This research offers an original contribution by connecting the economic dimensions of hate speech production with the socio-religious responses to it—an intersection that has received limited attention in studies of media and digital politics in Indonesia.